Monopolar hook electrode assisted laparoscopic resection of descending colon cancer - Wang, Junjiang; Yang, Zifeng; Feng, Xingyu; Zheng, Jiabing; Yao, Xueqing; Li, Yong (Translational Cancer Research; Vol 5, No 4 (August 08, 2016): Translational Cancer Research (Focused Issue: Radiomics in Radiation Oncology), 2016)
Colorectal cancer accounts for about 25% of all malignant tumors in China. Efficacy and safety of laparoscopic assisted descending colon cancer radical resection have been recognized, and that complete mesocolic excision (CME) plays an important role. For this surgery, most surgeons choose scalpel as the primary instrument, and monopolar hook electrode minimal. A 72-year-old female patient with an adenocarcinoma of the left colon, with pre-operative clinical stage CT3N1M0, was chosen for the study. We use the monopolar hook electrode to finish the laparoscopic assisted descending colon cancer radical resection. The tumor with the surrounding tissue and 4/15 lymph nodes was resected by laparoscopy and colon side to side anastomosis performed. The procedure lasted about 120 minutes with minimal bleeding. Postoperative tumor biopsy revealed a tumor staging of T3N2M0 (IIIB). The patient recovered well following the procedure and was discharged after 4 days. The use of monopolar hook electrode in laparoscopy assisted descending colon cancer radical removal is safe, feasible and effective. The procedure is accurate, safe, provides ease of operating in a narrow space and is relatively inexpensive.